Anti-Hair Loss Potential of Perilla Seed Extracts: In Vitro Molecular Insights from Supercritical Fluid Extraction - Anurak Muangsanguan; Warintorn Ruksiriwanich; Pipat Tangjaidee; Korawan Sringarm; Chaiwat Arjin; Pornchai Rachtanapun; Sarana Rose Sommano; Korawit Chaisu; Apinya Satsook; Juan Manuel Castagnini (Foods)
Perilla seed has long been recognized in traditional diets for its health-promoting properties, but its potential role in hair loss prevention remains underexplored. This study compared three extraction methods—maceration (MAC), screw pressing (SC), and supercritical fluid extraction (SFE)—to determine their efficiency in recovering bioactive compounds and their effects on androgenetic alopecia (AGA)-related pathways. The SFE extract contained the highest levels of polyunsaturated fatty acids and tocopherols, while MAC uniquely recovered a broader range of polyphenols. Among all extracts, SFE-derived perilla seed extract showed the most consistent biological effects, promoting proliferation of human hair follicle dermal papilla cells (HFDPCs) by 139.4 ± 1.1% at 72 h (p < 0.05). It also reduced TBARS and nitrite levels in HFDPCs to 66.75 ± 0.62% of control and 0.87 ± 0.01 μM, respectively, indicating strong antioxidant and anti-inflammatory effects. Importantly, the SFE extract significantly downregulated SRD5A1-3 and TGF-β1 expression—key genes involved in androgen-mediated hair follicle regression—outperforming finasteride, dutasteride, and minoxidil in vitro by approximately 1.10-fold, 1.25-fold, and 1.50-fold, respectively (p < 0.05). These findings suggest that perilla seed extract obtained via supercritical fluid extraction may offer potential as a natural candidate to prevent hair loss through multiple biological mechanisms. These in vitro results support its further investigation for potential application in functional food or nutraceutical development targeting scalp and hair health.